Double Movements of Destruction and Regulation: Commodity Chains and a New Political Economy of the Environment - Roberts, J.; Carmin, JoAnn; Rudel, Thomas (Conference Papers – American Sociological Association, 2011)
Sociologists have examined the ways in which capitalism contributes to environmental degradation as well as how, in selected circumstances, it increases efficiency while reducing pollution and human injustices. In this review, we draw on Polanyi's concept of the double movement to illustrate how self regulating markets give rise to environmental degradation and inequities and, in response, how these conditions often stimulate the emergence of collective action in pursuit of regulatory and social reforms. This process is iterative, with capitalist initiated degradation of the environment followed by regulatory reform and then efforts to weaken the regulatory regimes. We illustrate how resource extraction contributes to environmental degradation and power inequalities, pollution from industrial production is unequally distributed among workers and communities, and how the desire to limit exposure to risk has opened new markets and led to policies that contribute to consumption.
Sociology
Keywords: capitalism; commodity chains; consumption (economics); double movement; environmental degradation; industries; pollution